A review of the eastern and southern African blind-snakes (Serpentes: Typhlopidae), excluding Letheobia Cope, with the description of two new genera and a new species - Broadley, Donald G.; Wallach, Van (Zootaxa, 2009)
All eastern and southern African species of Typhlopidae (excluding Letheobia) are reviewed with synonymies, diagnoses, and distribution maps. The 27 species from this region are arranged as follows: three species remain in Typhlops (with T. cuneirostris calabresii elevated to full species status), 16 species are transferred from Typhlops to a new genus endemic to Africa (including a new species described from Kenya), three species remain in Rhinotyphlops, four species are transferred from Rhinotyphlops to a new genus endemic to Africa (with R. schlegelii brevis and R. s. mucruso elevated to full species status), and one invasive species of Ramphotyphlops is included, which has been established in a few areas. Keys to the included species and all six African typhlopid genera are provided. A current taxonomic synopsis is provided for extralimital African and Southwest Asian typhlopid species.